A STUDY ON THE TEACHING DESIGN AND PRACTICE OF ZERO-BASED CHINESE CHARACTERS IN THAILAND PRIMARY SCHOOLS FROM THE THEORETICAL PERSPECTIVE OF " FLIPPED CLASSROOM":: A CASE STUDY OF KAJONENETIYUT SCHOOL IN PATHUM THANI, THAILAND - Yao, Zumin (Chinese Language and Culture Journal, 2021)
This thesis research is aimed at zero-based Thailand primary school students. and based on Flipped Classroom Learning Theory, this research systematically teaches Chinese characters, including strokes, Chinese character structure, components, the principle of making words etc., Students take the initiative to complete the task of learning Chinese characters before class, and carry out Chinese character learning activities in class. The purpose is to make students be active in Chinese character learning. after teaching practice, according to the teaching effect and questionnaire survey, analyze the problems of teachers and students. In response to related issues, put forward three suggestions: adjusting teachers’ teaching methods, setting up classroom management measures, and exploring effective classroom activities.